2021
DOI: 10.3390/vaccines9030247
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Attitudes towards COVID-19 Vaccination: An Online Survey in Slovenia

Abstract: While the problem of vaccine hesitancy is not new, it has become more pronounced with the new COVID-19 vaccines and represents an obstacle to resolving the crisis. Even people who would usually trust vaccines and experts now prefer to wait for more information. A cross-sectional online survey was conducted in Slovenia in December 2020 to find out the attitudes of the population regarding COVID-19 vaccination and the factors that affect these attitudes. Based on 12,042 fully completed questionnaires, we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 33 publications
9
97
1
3
Order By: Relevance
“…We estimated that the potential number of the subjects included in the mailing list for the survey was about 5000, but the rate of nurses who effectively opened the link of the LimeSurvey© platform is unknown. According to some published studies, the average reach is between 5 and 6% [ 23 ], but we can suppose a larger percentage due to the high HCW interest about COVID-19 vaccine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated that the potential number of the subjects included in the mailing list for the survey was about 5000, but the rate of nurses who effectively opened the link of the LimeSurvey© platform is unknown. According to some published studies, the average reach is between 5 and 6% [ 23 ], but we can suppose a larger percentage due to the high HCW interest about COVID-19 vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the statistical power of the study was limited and the real response rate among nurses is unknown. However, according to data from the literature that estimate the average reach to be between 5 and 6% [ 23 ], we can suppose that a large percentage of subjects who opened the link of the survey fulfilled the questionnaire. Regarding the sample size, the need to complete data collection among nurses in the short time period between the announcement of the vaccination campaign and its beginning (about one month) is the reason for the relatively limited number of subjects enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that factors associated with scientific knowledge are linked with COVID-19 vaccine attitudes (e.g., Petravić et al, 2021;Robertson et al, 2021;Sturgis et al, 2021). Educational levels were associated with COVID-19 vaccine refusal/hesitancy (Petravić et al, 2021;Robertson et al, 2021;Schwarzinger et al, 2021).…”
Section: Factors Associated With Covid-19 Vaccine Attitudesmentioning
confidence: 93%
“…Alali et al, 2021 , Grü ner and Kr ü ger, 2020 , Jain et al, 2021 , Jiang et al, 2021 , Kelekar et al, 2021 , Lucia et al, 2020 , Mascarenhas et al, 2021 , Pastorino et al, 2021 , Patelarou et al, 2021 , Petravić et al, 2021 , Riad et al, 2021 , Rosental and Shmueli, 2021 , Saied et al, 2021 , Szmyd et al, 2021 .…”
Section: Uncited Referencementioning
confidence: 99%